POLITIK MANAJEMEN PENGELOLAAN SUMBER DAYA ALAM - Eka Putri, Nora (Humanus, 2013)
Decentralization has become an important factor in managing smaller administrative region. The regional autonomy ruled by the central government through the legislation UU No. 32 in 2004 about Regional Government is expected to improve the outcome of policies of Indonesia’s local administration. One of the authorities delegated to the local administration is the responsibility to manage the natural resources, which is important in increasing the regional income for the development of the communities. However, the implementation of natural resource management still cause several problems such as environmental degradation, poverty, and income inequality. In order to solve the problems, politics play an important role in the regional policy making including the planning, budgeting, implementing and monitoring the policy as well as maximizing the role of communities’ participation. This cooperation between the local administration is expected to result in the effective, efficient, fair, and sustainable use of natural resources. Key words: natural resources management, politics of management, local administration